DINAMIKA KARAKTERISTIK HABITAT MANGROVE HASIL REHABILITASI DI PANTAI UTARA PEMALANG JAWA TENGAH - , Kristo Damanik ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Mangrove destruction is always identical with habitat destruction, therefore recovery efforts can be directed to the improvement of their habitat. This research was conducted in the area of mangrove rehabilitation Mojo Pemalang district of Central Java province to observed the dynamics of the characteristics of the mangrove habitat rehabilitation at various ages. The results of this study are expected to provide an overview of the development of the characteristics of the mangrove habitat rehabilitation on the North Coast of Central Java. The study was done by determining the plot as 6 in each year of planting that design adapted to the zoning system in the mangrove forest. At each PU was measured diameter and species name of vegetation, environmental factors (salinity, dissolved oxygen, temperature, pH, thickness of mud), plankton, and nekton to see the differences in each habitat factor in each year of planting. The data were analyzed with ANOVA model (analysis of variances) and a further difference test using LSD (least significant differences). The results showed that there has been a change in the mangrove habitat rehabilitation karaketristik as impact of vegetation growth. that include: (1) a significant decrease in vegetation density and followed the growth of Avicennia alba, Avicennia marina and Rhizophora apiculata naturally. (2) significant temperature and salinity decreases, a significant increase both of dissolved oxygen (DO) and the thickness of the mud, but also no changes in pH (3) an increase in the density of plankton with the value of the high diversity index 3.60 (Shannon). Increased plankton was also followed by a significant increase in the abundance of nekton but does not change the index diversity and index dominance of nekton significantly. These results show that the dynamics characteristics of mangrove rehabilitation habitat occur temporally.